Local and regional variability in utilization and allocation of hepatitis C virus–infected hearts for transplantation. Issue 10 (10th April 2020) - Prakash, Katya; Wainana, Charles; Trageser, Jeffrey; Hahn, Ashley; Lay, Cecilia; Pretorius, Victor; Adler, Eric; Aslam, Saima
Abstract : With the advent of direct‐acting antiviral agents, there has been a rapid rise in hepatitis C virus–infected (HCV+) heart transplantation. We aimed to understand local and regional differences in utilization and allocation of HCV+ hearts. Using United Network for Organ Sharing (UNOS) de‐identified data from January 1, 2016 to September 30, 2019 we compared trends in the utilization rates (hearts transplanted/donors recovered) of HCV‐uninfected (HCV−) to those of HCV+ nonviremic (HCV‐NV) and viremic (HCV‐V) hearts nationally and by UNOS region. We also evaluated allocation rates (hearts successfully allocated/donors recovered) by organ procurement organization (OPO). We found that (1) in 2019, national utilization rates for HCV‐NV and HCV‐V hearts were the same as HCV− hearts (27.6% for HCV‐NV, 30.9 for HCV‐V, and 31.7% for HCV−, P  = .277); (2) utilization rates of HCV‐NV hearts were low in regions 3 and 4 and of HCV‐V hearts in regions 3, 4, and 8 even in the contemporary period since 2018; and (3) there was marked variability in allocation of HCV+ hearts at the OPO level even within the same UNOS region. We conclude that despite national strides in the utilization of HCV+ hearts for transplantation, more aggressive allocation of HCV+ hearts at the OPO level may still significantly affect the organ shortage. Abstract : In spite of equivalent utilization of HCV‐uninfected, HCV‐nonviremic, and HCV‐viremic hearts at the national level by 2019, significant variability exists at the regional and organ procurement organization levels.